Memahami Pengenaan Pajak Pertambahan Nilai (PPN) dalam Transaksi E-commerce - Muhammad Rafi Wijdan Hibatullah; Muhammad Ichwan Ardianto; Rahadyan Wijang Priambodo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology has fundamentally transformed economic transaction patterns in society, particularly through the widespread adoption of e-commerce that operates across borders and without physical presence. This condition poses new challenges to Indonesia's taxation system, especially in the imposition of Value Added Tax (VAT) which was originally designed to accommodate conventional transactions. This study aims to juridically analyze the regulation of VAT objects on e-commerce transactions, their collection mechanisms, and the various implementation challenges faced in Indonesia's tax practice. The method employed is normative juridical legal research using statutory, conceptual, and analytical approaches, drawing on primary, secondary, and tertiary legal sources. The findings indicate that juridically, VAT imposition on e-commerce transactions is not distinguished from conventional transactions, as affirmed through various regulations ranging from SE-62/PJ/2013 to the Tax Harmonization Law Number 7 of 2021. Nevertheless, its implementation still faces serious challenges, including difficulties in determining tax jurisdiction, the irrelevance of the Permanent Establishment (PE) concept to digital business actors, and low tax compliance among digital SMEs. In response, the government has implemented the AI-, big data-, and blockchain-based Coretax DJP system, effective January 1, 2025, to strengthen digital tax administration. This study concludes that VAT imposition in e-commerce serves as a crucial instrument not only for optimizing state revenue, but also for realizing fiscal justice between digital and conventional business actors.